Social Justice Theory in Indonesia Reviewed from the Philosophy of Law - Habib, Yahya Abdul; Gilalo, Jacobus Jopie (IJBLE Scientific Publications Community Inc., 2025)
Social justice theory occupies an important position in forming and implementing legal policies in Indonesia. This concept underscores the importance of equitable distribution of resources, opportunities, and legal protection without discrimination. This article discusses the challenges and implementation of social justice from the perspective of legal philosophy, focusing on the role of Pancasila as the basic ideology of the state. In the Indonesian context, the implementation of social justice often faces obstacles such as corruption, inefficient bureaucracy, and lack of access to the justice system for vulnerable groups. This article uses a descriptive qualitative approach to explore potential solutions such as legal reform, bureaucratic digitalization, and strengthening legal aid mechanisms. This research emphasizes that social justice is not only related to economic aspects but also includes fundamental human rights in various fields, including education, health, and general welfare. The goal of social justice as a national ideal can be achieved through inclusive policies and fair implementation of laws.